2020
DOI: 10.1186/s12879-020-4813-6
|View full text |Cite
|
Sign up to set email alerts
|

Determining the susceptibility of carbapenem resistant Klebsiella pneumoniae and Escherichia coli strains against common disinfectants at a tertiary hospital in China

Abstract: Background: Carbapenem-resistant Enterobacteriaceae (CRE) infections have become a global health threat. Controlling CRE transmission in hospitals is increasingly dependent on the use of disinfectants to restrict the risk of infection. Here, the susceptibility of patient-derived carbapenem resistant Klebsiella pneumoniae (CRKP) and Escherichia coli (CREC) strains against three common disinfectants and the determinants of resistance to disinfectants were investigated. Methods: The minimum inhibitory concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
24
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 21 publications
5
24
0
2
Order By: Relevance
“…Moreover, it has been described that the qacEΔ1 gene is located in an integron class 1 structure upstream of the sul1 gene that confers sulfonamide resistance and is often flanked by the dihydrofolate reductase gene dfrA1 related to trimethoprim resistance [18]. These gene cassette structures are related to the CHG tolerance, and TMP/SMX resistance found in our study (p < 0.05), with both genes likely being disseminated together in the same mobile structure within the same plasmid.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…Moreover, it has been described that the qacEΔ1 gene is located in an integron class 1 structure upstream of the sul1 gene that confers sulfonamide resistance and is often flanked by the dihydrofolate reductase gene dfrA1 related to trimethoprim resistance [18]. These gene cassette structures are related to the CHG tolerance, and TMP/SMX resistance found in our study (p < 0.05), with both genes likely being disseminated together in the same mobile structure within the same plasmid.…”
Section: Discussionsupporting
confidence: 56%
“…Our results correlate with a previous study performed in China that suggested decreased sensitivity against commonly used disinfectants, including CHG, in carbapenem-resistant strains. Furthermore, Chen et al [18] reported the presence of carbapenem-resistant K. pneumoniae with decreased susceptibility to CHG (MIC 32 µg/ml, which is the limit of the ecological cutoff of 64 µg/ml). It is important to mention that only six phylogenetically related strains were included in the study and all carbapenemases that were found were bla NDM [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Analyzing the log 2 (MIC) values reported for 45 antibiotic resistant strains, including carbapenem-resistant [ 18 ], extended spectrum beta-lactamase expressing cells [ 8 ], or strains expressing the New Delhi metallo-beta-lactamase [ 10 ], showed a mean (± Std Dev) of 4.14 (± 1.54) log 2 (MIC) units for the pooled antibiotic-resistant strains. This is different than the mean of all other strains (n = 2134) with mean = 1.81 (± 1.69) log 2 (MIC) units.…”
Section: Resultsmentioning
confidence: 99%
“…Articles were published between 1976 and 2021, although the majority (95%) were published this century. The antiseptics used included five different CHX salts (digluconate (33,35,37,40,47,50,(55)(56)(57)(58)61,63,67,69,74,75,81,83,88,90,94,97,99,101,106,107,111,113), gluconate (34,36,42,42,53,91,102,103,108,108,109,112), dichlorohydrate (85)(86)(87), diacetate (71,99) and dihydrochloride( 96)) and povidone-iodine (37,46,49,…”
Section: Study Characteristicsmentioning
confidence: 99%